Nonadherence in Hypertension: How to Develop and Implement Chemical Adherence Testing. Issue 1 (5th November 2021) - Lane, Dan; Lawson, Alexander; Burns, Angela; Azizi, Michel; Burnier, Michel; Jones, Donald J.L.; Kably, Benjamin; Khunti, Kamlesh; Kreutz, Reinhold; Patel, Prashanth; Persu, Alexandre; Spiering, Wilko; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Nonadherence to antihypertensive medication is common, especially in those with apparent treatment-resistant hypertension (true treatment-resistant hypertension requires exclusion of nonadherence), and its routine detection is supported by clinical guidelines. Chemical adherence testing is a reliable and valid method to detect adherence, yet methods are unstandardized and are not ubiquitous. This article describes the principles of chemical adherence testing for hypertensive patients and provides a set of recommendations for centers wishing to develop the test. We recommend testing should be done in either of two instances: (1) in those who have resistant hypertension or (2) in those on 2 antihypertensives who have a less than 10 mm Hg drop in systolic blood pressure on addition of the second antihypertensive medication. Furthermore, we recommend that verbal consent is secured before undertaking the test, and the results should be discussed with the patient. Based on medications prescribed in United Kingdom, European Union, and United States, we list top 20 to 24 drugs that cover >95% of hypertension prescriptions which may be included in the testing panel. Information required to identify these medications on mass spectrometry platforms is likewise provided. We discuss issues related to ethics, sample collection, transport, stability, urine versus blood samples, qualitative versus quantitative testing, pharmacokinetics, instrumentation, validation, quality assurance, and gaps in knowledge. We consider how to best present, interpret, and discuss chemical adherence test results with the patient. In summary, this guidance should help clinicians and their laboratories in the development of chemical adherence testing of prescribed antihypertensive drugs.